(untitled) (Research, Society and Development, 2019)
The present study sought to evaluate active methodologies in teaching-learning process through seminars together with flipped classroom technique as an educational tool. Undergraduates of General Chemistry from the Engineering courses of the Universidade Federal de Itajubá, in Minas Gerais, participated in this project. The proposal constituted in presentation of three themes associated to chemical bonds: Lewis Structure, Octet Rule and Ionic Bonds. Thus, the class was divided into teams and a particular theme was assigned for each one. The evaluation of the method as effective or not was carried out considering the opinion of the students through a questionnaire. The results obtained were satisfactory, since the most of the students contributed positively to the conclusion of the presentations. Through this study, it is concluded that the active methodologies are responsible for promote social and academic skills in the students, such as discussion, argumentation, oratory and listening comprehension of the environment, giving a greater dynamism to the learning process.